(untitled) (KULT_online, 2023)
The publication Ethik für Designer is structured into three main chapters, which focus on the basics of ethics principles, historical ideas of morality and necessary contemporary transformation processes regarding design perspectives. Ethical standards are reflected in temporal and cultural contexts to which design should respond or provide direction. Drawing on different philosophical theories on ethics, virtues and morality the author provides solutions and transfers them to design action.